Collaborative Inquiry: A Professional Learning Approach for Middle School Mathematics Teachers - Wong, Tsae (Curtin University, 2016)
This grounded theory study used the collaborative inquiry approach to deliver on-site built-in professional learning opportunities for middle school year teachers during their programmed year level planning time to discuss, deliberate and share pedagogical practices so as to grow their professional practice. The findings of this research ascertained the importance of such an on-site built-in professional learning model which found to be effective in developing a shared positive teachers’ disposition and to initiate pedagogical change.